Patient experiences of awake craniotomy: An Interpretative Phenomenological Analysis. (November 2016) - Howie, Emma; Bambrough, Jacki; Karabatsou, Konstantina; Fox, John RE
Awake craniotomy with language mapping enables maximum resection of tumours in eloquent areas while preserving function. This study aims to understand the lived experiences of those undergoing an awake craniotomy. Six participants who underwent awake craniotomy were interviewed, and the data were analysed using Interpretative Phenomenological Analysis. Themes were identified as 'Unspeakable Fear', 'Dissociation' and 'Control and Responsibility'. Participants discussed how surgery was a threat to the sense of self. Dissociation during surgery operated as a protective mechanism, while the surgical team all had roles in maintaining this bubble of dissociation, such as being a support to the patient's emotional needs.